Bibliometric Analysis of The Artificial Intelligence- Accounting Binomial - Gabriela STAFIE; Veronica GROSU; Marian SOCOLIUC; Simona-Maria BRINZARU (Communications of International Proceedings, 2021)
Artificial Intelligence (AI) is increasingly present in our lives that depends more and more on technology, but this context does not mean that the robots will replace us, but they will be our “partners.” The accounting profession uses technology to improve its professional’s work and to add value to the entities, fact that can be seen as an opportunity to optimize the quality of investment or business decisions. Professional accountants need to consider the innovative solutions such as AI and automation as valid opportunities and not threats, because these new technologies will definitely make our lives easier. This research paper aims to identify using the cluster method how to polarize the two key concepts that make up the accounting-AI binomial in research conducted so far and indexed in WoS and Scopus, in order to determine future development directions regarding the implementation of AI in accounting. The obtained results are concretized in the development of a bibliometric analysis of the Accounting - AI binomial with the help of the clusters that have been consolidated around these key concepts.
Keywords: Artificial Intelligence; Accounting; Bibliometric Analysis; VOSviewer